2022
DOI: 10.1186/s12891-022-05302-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of lumbar disc degeneration with low back pain in middle age in the Northern Finland Birth Cohort 1966

Abstract: Background Although it has been suggested that lumbar disc degeneration (LDD) is a significant risk factor for low back pain (LBP), its role remains uncertain. Our objective was to clarify the association between LDD and LBP and whether mental distress modifies the association. Methods Participants of a birth cohort underwent 1.5-T lumbar magnetic resonance imaging at the age of 47. The association between the sum score of LDD (Pfirrmann classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Survivors had an increased prevalence of lumbar disc herniations, but further studies are required to better understand the long-term consequences of IVD in this population. Lumbar IVD degeneration is associated with low back pain [16,17]. A previous publication of the same BT survivor population showed a trend toward reporting increased pain compared to healthy controls, but this association did not reach signi cance [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Survivors had an increased prevalence of lumbar disc herniations, but further studies are required to better understand the long-term consequences of IVD in this population. Lumbar IVD degeneration is associated with low back pain [16,17]. A previous publication of the same BT survivor population showed a trend toward reporting increased pain compared to healthy controls, but this association did not reach signi cance [27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that IVD degeneration can be identi ed in childhood; however, the prevalence increases with age [15]. Soon after the phase of rapid physical growth, individuals with lumbar IVD have an increased risk of recurrent lower back pain; in adulthood, individuals are predisposed to long-term risk of recurrent pain [14][15][16][17][18]. Early disc degeneration, if detected, may result in long-term recurrent pain in the survivors and further decrease their health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…A fourth expert rater determined the consensus Pfirrmann grade. 15 For historical reasons, Pfirrmann grades 1 and 2 were considered as grade 2. MC were evaluated by two blinded raters with specific experience in MC evaluation, with an interrater reliability of κ = 0.82.…”
Section: Datamentioning
confidence: 99%
“…However, should the possible clinical relevance of MRI findings of disc degeneration be discounted? Studies, including a systematic review, have found that overall prevalence of disc degeneration and of degenerative features, such as Modic changes [4], were significantly greater in those with LBP, than in asymptomatics [5][6][7]. But others find no such relationship [8,9].…”
Section: Introductionmentioning
confidence: 99%